Choroidal Volume Variations with Age, Axial Length, and Sex in Healthy Subjects: A Three-Dimensional Analysis - Barteselli, Giulio; Chhablani, Jay; El-Emam, Sharif; Wang, Haiyan; Chuang, Janne; Kozak, Igor; Cheng, Lingyun; Bartsch, Dirk-Uwe; Freeman, William R. (Ophthalmology (Rochester, Minn.), 2012)
To demonstrate the 3-dimensional choroidal volume distribution in healthy subjects using enhanced depth imaging (EDI) spectral-domain optical coherence tomography (SD-OCT) and to evaluate its association with age, sex, and axial length. Retrospective case series. A total of 176 eyes from 114 subjects with no retinal or choroidal disease. The EDI SD-OCT imaging studies of healthy patients who had undergone a 31-raster scanning protocol on a commercial SD-OCT device were reviewed. Manual segmentation of the choroid was performed by 2 retinal specialists. A macular choroidal volume map and 3-dimensional topography were automatically created by the built-in software of the device. Mean choroidal volume was calculated for each Early Treatment Diabetic Retinopathy Study (ETDRS) subfield. Regression analyses were used to evaluate the correlation between macular choroidal volume and age, sex, and axial length. Three-dimensional topography and ETDRS-style volume map of the choroid. Three-dimensional topography of the choroid and volume map was obtained in all cases. The mean choroidal volume was 0.228±0.077 mm3 for the center ring and 7.374±2.181 mm3 for the total ETDRS grid. The nasal quadrant showed the lowest choroidal volume, and the superior quadrant showed the highest choroidal volume. The temporal and inferior quadrants did not show different choroidal volume values. Choroidal volume in all the EDTRS rings was significantly correlated with axial length after adjustment for age (P < 0.0001), age after adjustment for axial length (P < 0.0001), and sex after adjustment for axial length (P < 0.05). Choroidal volume decreases by 0.54 mm3 (7.32%) for every decade and by 0.56 mm3 (7.59%) for every millimeter of axial length. Male subjects have a 7.37% greater choroidal volume compared with that of female subjects. Enhanced depth imaging SD-OCT is a noninvasive and well-tolerated procedure with an excellent ability to visualize 3-dimensional topography of the choroid and to measure choroidal volume at the posterior pole using manual segmentation. Age and axial length are inversely correlated with choroidal volume, most likely leading to changes in retinal metabolic support in elderly, highly myopic patients. Sexual differences should be considered when interpreting an EDI SD-OCT scan of the choroid. The author(s) have no proprietary or commercial interest in any materials discussed in this article.